Utilization of food waste streams for the production of biopolymers - Saranya Ranganathan; Sayantani Dutta; J.A. Moses; C. Anandharamakrishnan (Heliyon, 2020)
Uncontrolled decomposition of agro-industrial waste leads to extensive contamination of water, land, and air. There is a tremendous amount of waste from various sources which causes serious environmental problems. The concern in the disposal problems has stimulated research interest in the valorization of waste streams. Valorization of the wastes not only reduces the volume of waste but also reduces the contamination to the environment. Waste from food industries has great potential as primary or secondary feedstocks for biopolymer production by extraction or fermentation with pre-treatment or without pre-treatment by solid-state fermentation to obtain fermentable sugars. Various types of waste can be used as substrates for the production of biomaterials but recently more focus has been observed on the agro-industrial wastes which have a high rate of production worldwide. This review collates in detail the different food wastes used for biopolymer, technologies for the production and characterization of the biopolymers, and their economic/technical viability.